Trends, Differentials, and Social Determinants of Maternal Health Care Services Utilization in Rural India: An Analysis from Pooled Data - Arvind Kumar Yadav; Bhavna Sahni; Pabitra Kumar Jena; Dinesh Kumar; Kiran Bala (Mary Ann Liebert, 2020)
Background: Millennium development goal 5 aimed at reduction of maternal deaths by three-quarters from 1990 to 2015: a target India commendably achieved, but this milestone remains overshadowed by inequalities in utilization of health services that are driven by determinants both at community and at individual level. Materials and Methods: We studied the utilization trends using descriptive statistics and analyzed the relative contribution of various socioeconomic predictors on the use of maternal health care services in rural India using binary logistic regression analysis on pooled data from three rounds of National Family Health Survey. Outcome variables included four or more antenatal care visits, skilled birth attendance, and postnatal care. Results: Although utilization of maternal health care services showed an upward trend from 1998?1999 to 2015?2016, factors such as illiteracy, female age ?40 years, having five and more children, belonging to scheduled tribes, rural residence, and not possessing a health card were associated with significantly low utilization of maternal health care services. However, partner's education, good economic status, women's autonomy, and infrastructure at village level were associated with better odds of availing these services. Conclusions: The study generates evidence on the role of various socioeconomic determinants in maternal health care utilization and identifies gaps that must be strategically addressed to reach sustainable developmental goal maternal mortality target of 70 deaths per 100,000 live births by 2030. It reemphasizes the need for ensuring convergence among different stakeholders while structuring maternal health policies so that health reforms can be accomplished effectively at all levels of health care.